Measurement of the Performances of Various Asphalt Mixtures on Suspended Steel Deck Bridge Pavements - Eren, Caglar; Ozen, Halit; Sahin, Onur; Aygormez, Yurdakul (SPRINGERNATURE, 2025)
Asphalt mixtures are world widely used in various areas and one of them is on bridges as a pavement layer. The flexibility against oscillations, role in water discharge, and resistance against corrosion effects provided by asphalt mixtures are its important features. In terms of these important properties, the performance of asphalt mixtures in steel deck bridge coatings is a subject that needs to be investigated in detail. Various problems such as rutting and fatigue cracking may occur during the operation and construction of bridges built with a high construction budget. In this respect, it is expected that the coating materials chosen for the long-lasting use of the bridges will reduce operating and maintenance costs while increasing the comfort and safety of the road. For this study, various asphalt mixtures and structural designs were evaluated on steel deck bridges with their performances. The mixture types used on steel deck bridge pavements were mastic asphalt (MA), stone mastic asphalt (SMA), and modified mastic asphalt (MMA), and the structural designs were MA layer only, MA + SMA layer, and MA + MMA layer. The mixtures SMA and MMA were prepared by Marshall Method and MA was prepared by ZTV Asphalt STB 07 method. Then, Hamburg Wheel Tracking (HWT) test as a rutting test, and TS EN 12697-24 cyclic fatigue test as a fatigue test were applied for all different mixture types and various structural designs. Based on the results, the best performance belongs to MA + SMA in all tests and it is suggested to be used on steel deck bridge pavements to provide a higher contribution to water resistivity by MA and higher resistance to permanent deformations by SMA.
Keywords: Pavements; Asphalt mixtures; Steel deck bridge; Fatigue test; STONE MASTIC ASPHALT; FATIGUE BEHAVIOR; SYSTEMS; Construction & Building Technology; Engineering; Materials Science